PUBLIC HEALTH GOVERNANCE AND SOCIAL TRUST: LESSONS FROM GLOBAL HEALTH CRISES - Sarah Zielda Najib; Nurul Hidayati; Teguh Setiawan Wibowo; Roya Zahir (Yayasan Adra Karima Hubbi, 2026)
Public health governance has become a critical determinant of societal resilience as recent global health crises have demonstrated that effective emergency responses depend not only on healthcare capacity but also on institutional legitimacy, transparent decision-making, and public trust. Persistent variation in policy compliance and crisis outcomes across countries has intensified interest in understanding how governance quality influences collective behavioral responses during public health emergencies. This study aimed to examine the relationship between public health governance, institutional transparency, social trust, and community resilience across diverse national contexts. A mixed-methods sequential explanatory design was employed involving 3,600 respondents from twelve countries representing different governance systems and public health capacities. Quantitative data were collected using validated measures of governance effectiveness, institutional trust, policy compliance, communication credibility, healthcare preparedness, and community resilience, and analyzed through multilevel modeling, structural equation modeling, mediation analysis, and hierarchical regression. Qualitative evidence was obtained through semi-structured interviews, focus group discussions, policy document analysis, and institutional case studies, followed by thematic interpretation. Findings revealed that governance effectiveness significantly strengthened institutional trust, while transparent communication and information credibility enhanced policy compliance, vaccination acceptance, and community resilience. Community resilience further reinforced the positive relationship between institutional trust and behavioral compliance during health emergencies. Results indicate that sustainable public health governance requires coordinated institutional leadership, evidence-based communication, transparent policymaking, and meaningful public engagement. The proposed governance framework offers practical guidance for strengthening institutional resilience and social trust during future global health crises.